2021
DOI: 10.3390/ijerph18147319
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series Study of Help-Seeking among Younger and Older Men in Suicidal Crisis

Abstract: Due to the continuing high suicide rates among young men, there is a need to understand help-seeking behaviour and engagement with tailored suicide prevention interventions. The aim of this study was to compare help-seeking among younger and older men who attended a therapeutic centre for men in a suicidal crisis. In this case series study, data were collected from 546 men who were referred into a community-based therapeutic service in North West England. Of the 546 men, 337 (52%) received therapy; 161 (48%) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 54 publications
(97 reference statements)
0
30
0
Order By: Relevance
“…Half of the studies directly refer to co‐production as a methodological approach in the design of the suicide prevention intervention. 38 , 39 , 41 , 42 , 43 , 45 , 46 None of the studies provide an explicit definition of co‐production. Rather, most individual studies were found to integrate key elements of co‐production within the design and/or delivery of an intervention by involving stakeholders, representing the diverse modes in which co‐production can be applied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half of the studies directly refer to co‐production as a methodological approach in the design of the suicide prevention intervention. 38 , 39 , 41 , 42 , 43 , 45 , 46 None of the studies provide an explicit definition of co‐production. Rather, most individual studies were found to integrate key elements of co‐production within the design and/or delivery of an intervention by involving stakeholders, representing the diverse modes in which co‐production can be applied.…”
Section: Resultsmentioning
confidence: 99%
“…Delivery of the intervention by former professional sportspeople who recalled their lived experience of mental illness/ adversity was perceived to possibly studies. Stakeholders included health professionals, clinicians, mental health specialists, police officers, [38][39][40][41][42][43][44][45][46][47][48][49] community representatives including sporting representatives (e.g., ex-rugby players) and community leaders, 38,[40][41][42][43]45,46 YouTubers, 50 those who are representative of theor with lived experience/or with lived experience. 38,[40][41][42][43]45,46,[48][49][50][51]…”
Section: Definition and Operationalization Of Co-productionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, older had higher depression and anxiety (Tang et al , 2021). Saini et al (2021) also point out that older men were significantly more likely to have an absence of positive future thinking. It is worth noting that the belief that the Coronavirus is a greater threat to older adults in China is the possible reason for the older having more fears for COVID-19.…”
Section: Discussionmentioning
confidence: 99%